IMPLEMENTATION OF ISLAMIC BOARDING SCHOOL RULES IN ESTABLISHING STUDENT DISCIPLINE IN JAGAD ‘ALIMUSIRRY ISLAMIC STUDENT BOARDING SCHOOLS - Darojat, Zakiyatu (Journal Intellectual Sufism Research (JISR), 2019)
The current of globalization has led to competition in the world of education, so the education needed to make young people who are dignified, become responsible and democratic citizens. Islamic boarding schools as one of the institutions in non-formal education are tasked with forming the character and personality of the religion people to become a noble, noble and highly disciplined person. Formation of discipline through the order given so that students are able to become disciplined individuals by obeying the rules that have been made by Islamic boarding schools. Kyai and also boarding houses have an important role in the process of implementing the order.